Silicon oxide negative electrode material for solid-state lithium ion battery as well as preparation method, pre-lithiation method and application of silicon oxide negative electrode material
By using modified SiOx materials as negative electrode materials in solid-state lithium-ion batteries and adopting pre-lithiation methods, the problems of serious volume changes, low energy density and poor cycle performance in solid-state batteries are solved, achieving high energy density and cycle stability. sexual battery.
Patent Information
- Application Number
- CN202310904496.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
Existing solid-state lithium-ion batteries have problems such as serious changes in the volume of active substances, low energy density and poor circulation performance.
SiOx and/or modified SiOx materials are used as negative electrode materials, and their conductivity and cycle stability are improved through modification treatment, and the pre-lithiation method is used to improve the first Coulombic efficiency.
A solid-state battery with high specific energy, low expansion rate and high cycle stability has been achieved, which improves energy density and cycle stability and reduces battery production costs.
Smart Images

Figure CN119340382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and specifically, to a silicon oxide negative electrode material for solid-state lithium-ion batteries and a preparation method thereof, a pre-lithiation method and an application thereof; more specifically, to an application of a silicon oxide negative electrode material in a solid-state lithium-ion battery, a silicon oxide negative electrode material for a solid-state lithium-ion battery and a preparation method and a pre-lithiation method thereof, a silicon oxide negative electrode sheet and a preparation method thereof, a solid-state lithium-ion battery and electrical equipment. Background Art
[0002] Since its introduction, lithium-ion batteries have gradually occupied the fields of portable consumer electronics, power batteries and large-scale energy storage due to their excellent performance. With the continuous development and commercialization of its application in new energy vehicles, the safety and energy density of battery technology have gradually been paid attention to. The solid-state lithium-ion battery system is different from the existing commercial liquid lithium-ion battery system. The inside of the battery is in close contact with non-flammable solids, which can greatly improve the safety performance of the battery and also has broad prospects in the field of high energy density batteries.
[0003] The negative electrode materials of high energy density solid-state battery systems are generally silicon-based negative electrodes, lithium metal negative electrodes, and lithium-free negative electrodes. Metal lithium negative electrodes and lithium-free negative electrodes based on the electroplating / stripping mechanism are prone to lithium dendrites, thus causing safety problems and battery failure. The theoretical capacity of silicon negative electrode materials (Li 15 Si4, 3579 mAh / g; Li 22 Si5, 4200mAh / g) is about ten times that of the currently used graphite negative electrode, and has a suitable charge and discharge potential and abundant resources. However, the silicon negative electrode has a large volume expansion rate, which will cause great internal stress during the battery cycle (Li 15 Si4 about 300%; Li 22 Si5 is about 400%), which not only affects the battery cycle performance, but also brings challenges to battery pressure management.
[0004] CN110233282B discloses an all-solid-state battery containing a silicon negative electrode and a sulfide solid electrolyte, wherein the battery core includes a negative electrode, a solid electrolyte layer and a positive electrode, and the close contact structure can improve the physical contact of each material. However, the volume change of the silicon negative electrode is still too large and difficult to control.
[0005] CN111081990A discloses a composite negative electrode for an all-solid-state lithium-ion battery, which is in the form of a plurality of particles, each of which also has pores inside, and the average porosity of each particle is about 10%-75%. The porosity and internal space of the particles can alleviate the volume change of the solid-state battery, but this will reduce the energy density of the all-solid-state battery.
[0006] It can be seen that the solid-state batteries prepared by the existing scheme still have the problems of serious volume change of active materials and low energy density. Therefore, it is of great significance to develop a new negative electrode material with high specific capacity and small volume effect for high-safety solid-state batteries.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The first purpose of the present invention is to provide an application of silicon oxide negative electrode material in the negative electrode of a solid-state lithium-ion battery to solve the problems of serious volume change of active materials, low energy density and poor cycle performance in the solid-state battery in the prior art.
[0009] The second object of the present invention is to provide a silicon oxide negative electrode material for a solid-state lithium ion battery, wherein the silicon oxide negative electrode material has a low volume expansion rate and can improve the energy density and cycle stability of the solid-state lithium ion battery.
[0010] The third object of the present invention is to provide a method for preparing a silicon oxide negative electrode material for a solid-state lithium-ion battery, which can improve the conductivity, coulombic efficiency and cycle stability of the silicon oxide negative electrode material in the solid-state battery.
[0011] The fourth object of the present invention is to provide a pre-lithiation method for silicon oxide negative electrode materials for solid-state lithium-ion batteries, which can improve the first coulombic efficiency of silicon oxide negative electrode materials and thereby improve the energy density of solid-state batteries.
[0012] A fifth object of the present invention is to provide a silicon oxide negative electrode sheet having excellent electrochemical performance.
[0013] The sixth object of the present invention is to provide a method for preparing a silicon oxide negative electrode sheet.
[0014] A seventh object of the present invention is to provide a solid-state lithium-ion battery.
[0015] The eighth object of the present invention is to provide electrical equipment.
[0016] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0017] In a first aspect, the present invention provides an application of a silicon oxide negative electrode material in a solid-state lithium-ion battery negative electrode, wherein the silicon oxide negative electrode material comprises SiO x and / or modified SiO x Material, wherein 0<x<2.
[0018] In a second aspect, the present invention provides a silicon oxide negative electrode material for a solid-state lithium-ion battery, wherein the silicon oxide negative electrode material comprises SiO x and / or modified SiOx Material, wherein 0<x<2.
[0019] In a third aspect, the present invention provides a method for preparing the silicon oxide negative electrode material for solid-state lithium-ion batteries, wherein the modified SiO x The method for preparing the material includes at least one of the following methods (1) to (5):
[0020] (1) Using vapor deposition or liquid coating-carbonization method to deposit SiO x Carbon coating is performed to obtain carbon-coated SiO x Material;
[0021] (2) SiO x Mix evenly with carbon material to obtain SiO x / Carbon composite material; the carbon material comprises at least one of graphite, mesophase carbon microspheres, soft carbon and hard carbon;
[0022] (3) SiO x After mixing with dopants and sintering, element-doped SiO x The dopant comprises a doping element including at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn or an oxide thereof;
[0023] (4)SiO x Heat treatment is performed in an inert atmosphere to obtain heat-treated SiO x Materials; the heat treatment temperature is 800 to 1200° C., and the holding time is 0.5 to 20 hours; the heat treatment atmosphere includes an inert atmosphere;
[0024] (5)SiO x After mixing with a reducing agent, a reduction reaction is carried out to obtain reduced SiO x Material; the reducing agent includes at least one of metallic aluminum and metallic magnesium.
[0025] In a fourth aspect, the present invention provides a method for pre-lithiation of a silicon oxide negative electrode material for a solid-state lithium-ion battery, comprising the following steps:
[0026] The silicon oxide negative electrode material is mixed with a lithium supplement agent and ground; the lithium supplement agent comprises at least one of metallic lithium, lithium silicide, naphthyl lithium and biphenyl lithium;
[0027] And / or, the silicon oxide negative electrode material is made into a film, which is then stacked with a lithium sheet and pressurized for battery assembly.
[0028] In a fifth aspect, the present invention provides a silicon oxide negative electrode plate, which is mainly made of the silicon oxide negative electrode material for solid-state lithium-ion batteries;
[0029] Preferably, the silicon oxide negative electrode material is pre-lithiated by the pre-lithiation method.
[0030] In a sixth aspect, the present invention provides a method for preparing the silicon oxide negative electrode sheet, comprising the following steps:
[0031] Applying a first mixed material containing a silicon oxide negative electrode material and a solvent to the surface of a current collector; optionally, the first mixed material further comprises at least one of a carbon material, a conductive agent and an electrolyte;
[0032] And / or, after rolling the second mixed material containing the silicon oxide negative electrode material and the binder into a film, it is compounded with the current collector by hot pressing; optionally, the second mixed material also includes at least one of a binder, a carbon material, a conductive agent and an electrolyte.
[0033] In a seventh aspect, the present invention provides a solid-state lithium-ion battery, comprising the silicon oxide negative electrode sheet, a solid electrolyte and a positive electrode sheet; or comprising the silicon oxide negative electrode sheet, a semi-solid electrolyte and a positive electrode sheet;
[0034] Preferably, the solid electrolyte comprises at least one of an oxide, a sulfide, a polymer electrolyte and an organic-inorganic composite electrolyte;
[0035] Preferably, the active material used for the positive electrode plate includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, nickel-manganese layered oxide positive electrode material, lithium manganese oxide, lithium-rich manganese-based positive electrode material, sulfur and lithium sulfide.
[0036] In an eighth aspect, the present invention provides an electrical device comprising the solid-state lithium-ion battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The silicon oxide negative electrode material provided by the present invention is used in the negative electrode of a solid-state lithium-ion battery. Since the volume expansion rate of silicon oxide is low, using it as a negative electrode material can obtain a solid-state battery with high specific energy, low expansion rate and high cycle stability.
[0039] (2) The silicon oxide negative electrode material for solid-state lithium-ion batteries provided by the present invention uses unmodified SiO x and / or modified SiO x The material is used in solid-state lithium-ion batteries to improve the energy density and cycle stability of solid-state lithium-ion batteries.
[0040] (3) The preparation method of the silicon oxide negative electrode material for solid-state lithium-ion batteries provided by the present invention can further improve the electrochemical performance of the silicon oxide negative electrode material in solid-state batteries, that is, improve the conductivity, coulombic efficiency and cycle stability.
[0041] (4) The pre-lithiation method of silicon oxide negative electrode material for solid-state lithium-ion batteries provided by the present invention can improve the first coulombic efficiency of the silicon oxide negative electrode material, thereby improving the energy density of the solid-state battery.
[0042] (5) The silicon oxide negative electrode provided by the present invention has excellent electrochemical properties.
[0043] (6) The method for preparing the silicon oxide negative electrode plate provided by the present invention adopts a dry film-making process to reduce the use of solvents and is more compatible with sulfide-based solid electrolytes; and the dry film-making process can more efficiently mix the components in the negative electrode material, simplify the battery manufacturing process, and reduce the battery production cost.
[0044] (7) The solid-state lithium-ion battery provided by the present invention has high energy density, good safety performance, and excellent cycle stability performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 The charge and discharge curve diagram of the battery prepared in Example 1 of the present invention;
[0047] Figure 2 The charge and discharge curve diagram of the battery prepared in Example 2 of the present invention;
[0048] Figure 3 This is a rate performance test diagram of the battery prepared in Example 4 of the present invention;
[0049] Figure 4 This is a test diagram of the cycle performance of the battery prepared in Example 4 of the present invention;
[0050] Figure 5 The cyclic coulombic efficiency diagram of the battery prepared in Example 4 of the present invention;
[0051] Figure 6 This is a cross-sectional view of the negative electrode sheet of the battery prepared in Example 4 of the present invention after cycling;
[0052] Figure 7 This is a test diagram of the cycle performance of the battery prepared in Example 5 of the present invention;
[0053] Figure 8 The reduced SiO obtained in Example 6 of the present invention x XRD pattern of
[0054] Fig. 9 This is a test diagram of the cycle performance of the battery prepared in Example 6 of the present invention;
[0055] Fig.10 The charge and discharge curve diagram of the battery prepared in Example 7 of the present invention;
[0056] Fig.11 The charge and discharge curve diagram of the battery prepared in Example 8 of the present invention;
[0057] Fig.12 The charge and discharge curve diagram of the battery prepared in Example 9 of the present invention;
[0058] Fig.13 This is a cross-sectional view of the negative electrode sheet of the battery prepared in Comparative Example 2 of the present invention after cycling. DETAILED DESCRIPTION
[0059] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0060] In a first aspect, the present invention provides an application of a silicon oxide negative electrode material in a solid-state lithium-ion battery negative electrode, wherein the silicon oxide negative electrode material comprises SiO x (i.e., unmodified SiO x ) and / or modified SiO x Materials (i.e. SiO x After modified material), wherein 0<x<2, the value of x includes but is not limited to any point value among 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or the range value between any two of them.
[0061] SiO x and / or modified SiO x The material is a negative electrode material for solid-state lithium-ion batteries, and can obtain solid-state batteries with high specific energy and high cycle stability.
[0062] The solid-state lithium-ion batteries referred to in the present invention include all-solid-state batteries and semi-solid-state batteries. An all-solid-state battery refers to a battery that does not contain a liquid electrolyte and uses at least one of an oxide, a sulfide, a polymer electrolyte, or an organic-inorganic composite electrolyte; a semi-solid-state battery refers to a battery containing a partial liquid electrolyte, and the battery contains a certain amount of liquid electrolyte in addition to at least one of an oxide, a sulfide, a polymer electrolyte, or an organic-inorganic composite electrolyte. A semi-solid electrolyte refers to an electrolyte that contains a certain amount of liquid electrolyte in addition to at least one of an oxide, a sulfide, a polymer electrolyte, or an organic-inorganic composite electrolyte.
[0063] Silicon oxide has a wide range of sources and stable chemical and electrochemical properties. x ) itself has a high theoretical capacity and a low discharge potential, which can improve the energy density of solid-state lithium-ion batteries. Furthermore, compared with the silicon negative electrode, the volume expansion rate of silicon oxide is lower. During its first discharge process, silicon oxide is converted into lithium oxide, lithium silicate and silicon-lithium alloy, among which the silicon-lithium alloy is a reversible phase. After the first charge, the structure of silicon oxide is transformed into a framework network structure of lithium oxide and lithium silicate inlaid with nano-silicon microcrystals. In the subsequent charge and discharge process, the framework network structure can adapt to the volume change of microcrystalline silicon inside it, reduce the possibility of pulverization and cracking of the negative electrode material, and ensure the stability of each interface. In addition, lithium oxide and lithium silicate can also act as lithium-conducting phases to promote the migration of lithium ions inside the negative electrode and promote the electrochemical reaction of the negative electrode. In addition, silicon oxide has higher safety. Silicon oxide has a suitable charge and discharge potential, and its lithium storage mechanism is an alloying reaction, which is not easy to produce lithium dendrites.
[0064] Moreover, compared with liquid lithium-ion batteries, silicon oxide is more compatible with solid-state battery systems, including semi-solid-state batteries and all-solid-state batteries. First of all, the highly expandable negative electrode material in the liquid system is prone to material pulverization and shedding during the expansion and contraction process. Therefore, the content of silicon oxide in the negative electrode material of liquid lithium-ion battery silicon oxide needs to be controlled at a certain value. In solid-state batteries with a certain pressurization effect, close contact between particles can be guaranteed, and even if a full silicon oxide negative electrode is used, there will be no problem of material shedding. Secondly, the electrolyte material in the solid-state battery has a certain flexibility, which can alleviate the volume change while ensuring the conduction of lithium ions. Thirdly, in solid-state batteries, the contact area between the negative electrode material and the electrolyte can be reduced, and the continuous occurrence of side reactions at the interface can also be prevented.
[0065] In the present invention, SiO x (i.e., unmodified SiO x ) can be prepared by any conventional method in the prior art. For example, the gas phase method can be used to prepare SiO x , that is, condensing the high-temperature vaporized Si and SiO2 mixture. It can be understood that SiO x The x in can be controlled by adjusting the ratio of Si and SiO2 mixture.
[0066] In a preferred embodiment, the SiO x And / or the modified SiO x In the material, 0.4≤x≤1.3. By further controlling the range of x value, the conductivity of SiOx and modified SiOx materials can be increased, and the specific capacity and first coulombic efficiency of silicon oxide negative electrode materials can be improved.
[0067] In a preferred embodiment, the SiO x And / or the modified SiO x SiO in materials x (including SiO before modification x And the modified SiO x ) has a particle size of 0.1 to 20 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm or any range value between two thereof; more preferably 0.1 to 5 μm. Under this particle size distribution, the packing density and compaction density of the material can be increased, thereby ensuring close contact between particles, shortening the migration path of lithium ions, promoting solid phase diffusion of lithium ions and reducing contact impedance, thereby reducing polarization and improving SiO x Capacity utilization, coulombic efficiency and rate performance of materials.
[0068] It is understandable that SiO x The particle size of SiO can be regulated by grinding, such as ball milling. xThe particle size is also one of the modification methods, which is physical modification. In a preferred embodiment, the grinding specifically includes: ball milling at a speed of 200-600 r / min for 1-48 hours, wherein the speed includes but is not limited to any point value of 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min or any range value between two thereof, and the ball milling time includes but is not limited to any point value of 2 h, 4 h, 5 h, 10 h, 15 h, 20 h, 24 h, 28 h, 30 h, 32 h, 35 h, 40 h, 45 h or any range value between two thereof.
[0069] In a preferred embodiment, the modified SiO x Materials include carbon-coated SiO x Materials, SiO x / carbon composites, element-doped SiO x Materials, heat treated SiO x Materials and reduced SiO x At least one of the materials.
[0070] It is understandable that SiO x After modification by some methods, its microstructure can be regulated.
[0071] The present invention can further optimize the performance of silicon oxide in solid-state batteries by modifying the silicon oxide. Specifically, by means of carbon coating, doping, and composite with carbon materials, the defects of silicon oxide itself, such as low electronic conductivity, still high volume effect and low first coulomb efficiency, can be improved. At the same time, after modification, the electrochemical polarization of the negative electrode can be reduced, and the lithium insertion / delithiation reaction of silicon oxide can be promoted. In addition, by particle size control, inert atmosphere heat treatment, and reduction, the physical interfaces between particles and components within particles can also be optimized, a reasonable ion / electron transport network can be constructed, mass transfer between particles can be promoted, and the cycle stability can be improved.
[0072] The carbon-coated SiO x Material refers to SiO x A composite material having a carbon layer coated on the surface. The coating method may adopt any conventional coating method in the prior art, such as vapor deposition method and liquid coating-carbonization method, but is not limited thereto. In a specific embodiment, the carbon-coated SiO x The mass of the carbon coating in the material accounts for the carbon-coated SiO x 1% to 10% of the total mass of the material, including but not limited to any point value of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or a range of values between any two of them.
[0073] SiO x / Carbon composite materials refer to SiO x The material is mixed and compounded with carbon material. Preferably, the SiO x The carbon material in the SiO / carbon composite material includes at least one of graphite, mesophase carbon microspheres, soft carbon and hard carbon, wherein the graphite includes natural graphite and artificial graphite. x The preparation method of the SiO / carbon composite material specifically comprises: x and carbon material are mixed uniformly. In a specific embodiment, the mass of the carbon material accounts for x / 0% to 50% of the total mass of the carbon composite material, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or any point value thereof or a range value between any two of them.
[0074] Element-doped SiO x Material refers to SiO x Preferably, the element-doped SiO x The doping element in the material includes at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn. In a specific embodiment, the element-doped SiO x The preparation method of the material specifically comprises: x After being mixed evenly with the dopant, sintering is performed. The sintering temperature is 500-1600°C, including but not limited to any one of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or any range between two of them; the sintering holding time is 1-20h, including but not limited to any one of 3h, 5h, 8h, 10h, 13h, 15h, 18h or any range between two of them. The dopant includes a single substance or oxide of at least one element selected from B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn. The doping element is in SiO x The existing forms of silicon are oxides, silicates and alloys with silicon. The general formula of the doped material is SiM y O x (M is a doping element), where 0<x<2, 0.001 <y<2。
[0075] Heat treated SiO x Material refers to SiO xAfter the heat treatment, in a specific embodiment, the heat treatment is carried out in an inert atmosphere, and the SiO x The x value in the heat treatment is unchanged. x The material is SiO x The product is prepared by heat treatment under an inert atmosphere, wherein the heat treatment temperature is 800-1200°C, including but not limited to any one of 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or any range between two thereof; the heat treatment holding time is 0.5-20h, including but not limited to any one of 1h, 2h, 3h, 5h, 8h, 10h, 13h, 15h, 18h or any range between two thereof. The inert atmosphere includes nitrogen and / or argon.
[0076] After reduction, SiO x Material refers to SiO x After the material is reduced by the reducing agent, SiO x The x value in the reduced SiO x x in the material is ≤ 1.1. Preferably, the reduced SiO x The material is SiO x The reduced SiO x In the material, 0.4≤x≤1.1. More preferably, SiO x The mass ratio of the reducing agent is 1:0.5-2, including but not limited to any one of 1:0.8, 1:1, 1:1.3, 1:1.5, 1:1.8 or any range between them. More preferably, the reduction temperature is 300-900°C, including but not limited to any one of 500°C, 600°C, 700°C, 800°C, 850°C or any range between them; the insulation time of reduction is 0.5-20h, including but not limited to any one of 1h, 2h, 3h, 5h, 8h, 10h, 13h, 15h, 18h or any range between them.
[0077] In a second aspect, the present invention provides a silicon oxide negative electrode material for a solid-state lithium-ion battery, wherein the silicon oxide negative electrode material comprises SiO x and / or modified SiO xMaterial, wherein 0<x<2, the value of x includes but is not limited to any point value of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or the range value between any two of them.
[0078] Using unmodified SiO x and / or modified SiO x The material is used as a negative electrode material in solid-state lithium-ion batteries to improve the specific energy and cycle stability of solid-state lithium-ion batteries.
[0079] Among them, silicon oxide (SiO x ) has a wide range of sources and stable chemical and electrochemical properties.
[0080] Furthermore, silicon oxide itself has a higher theoretical capacity and a lower discharge potential, which can improve the energy density of solid-state lithium-ion batteries.
[0081] At the same time, compared with the silicon negative electrode, the volume expansion rate of silicon oxide is lower. During its first discharge process, silicon oxide is converted into lithium oxide, lithium silicate and silicon-lithium alloy, among which silicon-lithium alloy is a reversible phase. After the first charge, the structure of silicon oxide is transformed into a framework network structure of lithium oxide and lithium silicate inlaid with nano-silicon microcrystals. In the subsequent charging and discharging process, the framework network structure can adapt to the volume change of microcrystalline silicon inside it, reduce the possibility of pulverization and cracking of the negative electrode material, and ensure the stability of each interface. In addition, lithium oxide and lithium silicate can also act as lithium-conducting phases to promote the migration of lithium ions inside the negative electrode and promote the electrochemical reaction of the negative electrode.
[0082] In addition, silicon oxide has high safety. Silicon oxide has a suitable charge and discharge potential, and its lithium storage mechanism is an alloying reaction, which is not easy to produce lithium dendrites.
[0083] Furthermore, compared to liquid lithium-ion batteries, silicon oxide is more compatible with solid-state battery systems, including semi-solid-state batteries and all-solid-state batteries. First, highly expandable negative electrode materials are prone to material pulverization and shedding during expansion and contraction in liquid systems. Therefore, the content of silicon oxide in the negative electrode material of liquid lithium-ion battery silicon oxide needs to be controlled at a certain value. In solid-state batteries with a certain pressurization effect, close contact between particles can be guaranteed, so even if a full silicon oxide negative electrode is used, there will be no problem of material shedding. Secondly, the electrolyte material in the solid-state battery has a certain flexibility, which can alleviate volume changes while ensuring the conduction of lithium ions. In addition, in solid-state batteries, the contact area between the negative electrode material and the electrolyte can be reduced, and the continuous occurrence of side reactions at the interface can also be prevented.
[0084] In addition, by modifying silicon oxide, its performance in solid-state batteries can be further optimized.
[0085] In a preferred embodiment, SiO x The preparation method includes a gas phase method, that is, condensing a high-temperature vaporized Si and SiO2 mixture. Among them, x can be controlled by adjusting the ratio of the Si and SiO2 mixture.
[0086] In a preferred embodiment, the SiO x and / or modified SiO x In the material, 0.4≤x≤1.3, the x value in this range can increase SiO x and modified SiO x The conductivity of the material is improved, and the specific capacity and first coulombic efficiency of silicon oxide negative electrode materials are increased.
[0087] In a preferred embodiment, the SiO x And / or the modified SiO x SiO in materials x The particle size is 0.1-20 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm or any range value between two thereof; more preferably 0.1-5 μm.
[0088] In a preferred embodiment, the modified SiO x Materials include carbon-coated SiO x Materials, SiO x / carbon composites, element-doped SiO x Materials, heat treated SiO x Materials and reduced SiO x At least one of the materials.
[0089] The present invention can improve the defects of low electronic conductivity, high volume effect and low first coulomb efficiency of silicon oxide itself by adopting modification means such as carbon coating, doping and compounding with carbon materials. After modification, the electrochemical polarization of the negative electrode can be reduced and the lithium insertion / de-lithiation reaction of silicon oxide can be promoted.
[0090] In addition, the present invention can also optimize the physical interfaces between particles and components within particles through particle size control, inert atmosphere heat treatment, and reduction, construct a reasonable ion / electron transport network, promote mass transfer between particles, and thus improve cycle stability.
[0091] More preferably, the SiO xThe carbon material in the carbon / carbon composite material includes at least one of graphite, mesophase carbon microbeads, soft carbon and hard carbon.
[0092] More preferably, the element-doped SiO x The doping elements in the material include at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn elements.
[0093] More preferably, the heat-treated SiO x The material is SiO x The heat treatment is performed at a temperature of 800 to 1200°C, including but not limited to any one of 850°C, 900°C, 950°C, 1000°C, 1050°C, and 1100°C or a range between any two of them; the heat preservation time is 0.5 to 20h, including but not limited to any one of 1h, 2h, 3h, 5h, 8h, 10h, 13h, 15h, and 18h or a range between any two of them. The heat treatment atmosphere includes an inert atmosphere, such as at least one of a nitrogen atmosphere and an argon atmosphere.
[0094] More preferably, the reduced SiO x The material is SiO x The product is prepared by reduction, wherein the reducing agent used for the reduction comprises at least one of metallic aluminum and metallic magnesium.
[0095] In a third aspect, the present invention provides a method for preparing the silicon oxide negative electrode material for solid-state lithium-ion batteries, specifically, modified SiO x Preparation method of materials, modified SiO x The method for preparing the material includes at least one of the following methods (1) to (5):
[0096] (1) Using vapor deposition or liquid coating-carbonization method to deposit SiO x Carbon coating is performed to obtain carbon-coated SiO x Preferably, carbon-coated SiO x The mass of the carbon coating in the material accounts for the carbon-coated SiO x 1% to 10% of the total mass of the material, including but not limited to any point value of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or a range of values between any two of them.
[0097] (2) SiO x Mix evenly with carbon material to obtain SiO x / carbon composite material; the carbon material includes at least one of graphite, mesophase carbon microspheres, soft carbon and hard carbon. Preferably, the mass of the carbon material accounts for 1.3% of SiOx / 0% to 50% of the total mass of the carbon composite material, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or any point value thereof or a range value between any two of them.
[0098] (3) SiO x After mixing with dopants and sintering, element-doped SiO x Materials; the dopant includes a single substance or oxide of at least one of the doping elements B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn. Preferably, the sintering temperature is 500-1600°C, including but not limited to any point value of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or any range value between two of them; the holding time is 1-20h, including but not limited to any point value of 3h, 5h, 8h, 10h, 13h, 15h, 18h or any range value between two of them.
[0099] It is understandable that the doping elements in SiO x It exists in the form of oxides, silicates and alloys with silicon.
[0100] The general formula of the doped material is SiM y O x (M is a doping element), where 0<x<2, 0.001 <y<2。
[0101] (4)SiO x Heat treatment is performed in an inert atmosphere to obtain heat-treated SiO x The material; the heat treatment temperature is 800-1200°C, including but not limited to any one of 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or any range between two of them; the holding time is 0.5-20h, including but not limited to any one of 1h, 2h, 3h, 5h, 8h, 10h, 13h, 15h, 18h, 19h or any range between two of them. Preferably, the heat treatment is carried out under an inert atmosphere, which includes nitrogen and / or argon. SiO x The x values in are unchanged.
[0102] (5)SiO x After mixing with a reducing agent, a reduction reaction is carried out to obtain reduced SiO xMaterial; the reducing agent includes at least one of metallic aluminum and metallic magnesium.
[0103] Preferably, SiO x The mass ratio of the reducing agent to the reducing agent is 1:0.5-2, including but not limited to any one of 1:0.8, 1:1, 1:1.3, 1:1.5, 1:1.8 or a range between any two of them.
[0104] Preferably, the reduction temperature is 300-900°C, including but not limited to any one of 500°C, 600°C, 700°C, 800°C, 850°C or a range between any two of them; the reduction holding time is 0.5-20h, including but not limited to any one of 1h, 2h, 3h, 5h, 8h, 10h, 13h, 15h, 18h or a range between any two of them.
[0105] The above modified SiO x The material preparation method can further improve the electrochemical performance of silicon oxide negative electrode materials in solid-state batteries.
[0106] Specifically, the modified SiO x The material preparation method can improve the defects of silicon oxide itself, such as low electronic conductivity, high volume effect and low first coulomb efficiency; the method can reduce the electrochemical polarization of the negative electrode and promote the lithium insertion / delithiation reaction of silicon oxide.
[0107] In addition, the above method can also optimize the physical interfaces between particles and components within particles, construct a reasonable ion / electron transport network, promote mass transfer between particles, and thus improve cycle stability.
[0108] In a fourth aspect, the present invention provides a method for pre-lithiation of a silicon oxide negative electrode material for a solid-state lithium-ion battery, which specifically comprises the following steps:
[0109] The silicon oxide negative electrode material is mixed with a lithium supplement and ground; the lithium supplement includes at least one of metallic lithium, lithium silicide, naphthyl lithium and biphenyl lithium, wherein the metallic lithium can be a lithium element in any form, such as lithium powder, lithium sheet and lithium belt, but is not limited thereto.
[0110] Preferably, the grinding comprises ball milling; the grinding time is 2 to 20 hours, including but not limited to any one of 3 hours, 5 hours, 8 hours, 10 hours, 13 hours, 15 hours, and 18 hours or a range between any two of them.
[0111] Preferably, the mass of the lithium supplementer accounts for 30% to 70% of the total mass of the silicon oxide negative electrode material and the lithium supplementer, including but not limited to any one of 35%, 40%, 45%, 50%, 55%, 60%, 65% or a range between any two of them.
[0112] Preferably, a solvent is added during the grinding process. More preferably, the solvent includes one or more of n-hexane and ethylene glycol dimethyl ether.
[0113] And / or, the silicon oxide negative electrode material prepared by the dry method is made into a film and then laminated with a lithium sheet, and the battery is assembled under pressure to achieve negative electrode lithium replenishment.
[0114] The pre-lithiation method provided by the present invention can improve the first coulombic efficiency of silicon oxide negative electrode materials. Higher coulombic efficiency can improve the energy density of solid-state batteries.
[0115] In addition, pre-lithiated silicon oxide can be used as a lithium-containing negative electrode in high-energy-density solid-state battery systems, such as lithium-sulfur batteries and lithium-air batteries.
[0116] In a preferred embodiment, the pre-lithiation method further comprises: adding at least one of Li2NiO2, Li5FeO4, Li2O and Li2S to the positive electrode material.
[0117] In a fifth aspect, the present invention provides a silicon oxide negative electrode plate, which is mainly made of the silicon oxide negative electrode material for solid-state lithium-ion batteries.
[0118] In a preferred embodiment, the raw materials for preparing the silicon oxide negative electrode sheet also include at least one of a carbon material, a binder, a conductive agent, an electrolyte, a current collector and a solvent.
[0119] Preferably, the silicon oxide negative electrode material is pre-lithiated by the pre-lithiation method.
[0120] The silicon oxide negative electrode sheet has excellent electrochemical performance when used in solid-state lithium-ion batteries.
[0121] In a sixth aspect, the present invention provides a method for preparing the silicon oxide negative electrode sheet, and the method for preparing the silicon oxide negative electrode sheet includes a dry method and a wet method.
[0122] Among them, the method for preparing a silicon oxide negative electrode sheet by a wet process comprises the following steps: applying a first mixed material containing a silicon oxide negative electrode material and a solvent to the surface of a current collector. Optionally (referring to optional, not optional), the first mixed material also includes at least one of a carbon material, a conductive agent and an electrolyte. Specifically, each raw material can be dispersed in a solvent to obtain a first mixed material; and then the first mixed material is coated on the current collector. Preferably, the solvent includes at least one of toluene, n-heptane and N-methylpyrrolidone.
[0123] The method for preparing silicon oxide negative electrode sheets by dry method (i.e., dry film making) comprises the following steps: rolling a second mixed material containing silicon oxide negative electrode material and a binder into a film, and then compounding it with a current collector by hot pressing. Optionally (optional, not optional), the second mixed material also includes at least one of a binder, a carbon material, a conductive agent, and an electrolyte. Specifically, the raw materials can be dry mixed and then rolled into a film, and then compounded with the current collector by hot pressing.
[0124] The dry film preparation method can reduce the use of solvents and make it more compatible with sulfide-based solid electrolytes. In addition, the dry film preparation method can more efficiently mix the components of the negative electrode material, simplify the battery manufacturing process, and reduce the battery manufacturing cost.
[0125] In the above-mentioned dry and wet processes for preparing silicon oxide negative electrode sheets, the mass of the silicon oxide negative electrode material accounts for 70% to 99% of the total mass of the raw materials (referring to the sum of the masses of all raw materials except the current collector), including but not limited to any point value of 75%, 80%, 85%, 90%, 93%, 95%, 97% or any range value between two of them.
[0126] In the above-mentioned dry and wet methods for preparing silicon oxide negative electrode sheets, the carbon material used includes at least one of graphite, mesophase carbon microspheres, soft carbon and hard carbon, wherein the graphite includes natural graphite and / or artificial graphite. The mass of the carbon material accounts for 0.1% to 50% of the total mass of the raw materials, including but not limited to 1%, 3%, 5%, 7%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or any point value or range value between any two of them.
[0127] In the above-mentioned dry and wet processes for preparing silicon oxide negative electrode sheets, the binder used includes at least one of polytetrafluoroethylene, styrene-butadiene rubber, carboxymethyl cellulose salt, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, polyacrylamide, sodium alginate and chitosan, and the mass of the binder accounts for 0.1% to 10% of the total mass of the raw materials, including but not limited to any one of 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 5%, 7%, 9% or any range between two of them.
[0128] In the above-mentioned dry and wet processes for preparing silicon oxide negative electrode sheets, the conductive agent used includes at least one of carbon nanotubes, carbon black, vapor-deposited carbon fibers and graphene, and the mass of the conductive agent accounts for 0.1 to 10% of the total mass of the raw materials, including but not limited to any one of 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 5%, 7%, 9% or a range between any two of them.
[0129] In the above-mentioned dry and wet processes for preparing silicon oxide negative electrode sheets, the electrolyte used includes at least one of oxides, sulfides, polymer electrolytes, organic-inorganic composite electrolytes, and semi-solid electrolytes containing liquids. It is understandable that in the above-mentioned dry and wet processes for preparing silicon oxide negative electrode sheets, the type of electrolyte used can be the same as or different from the type of solid electrolyte used in solid-state lithium-ion batteries. The mass of the electrolyte accounts for 0.1 to 20% of the total mass of the raw materials, including but not limited to any point value of 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 5%, 7%, 9%, 10%, 12%, 15%, 18%, or any range value between the two.
[0130] In a preferred embodiment, the porosity of the silicon oxide negative electrode sheet is 10% to 25%, including but not limited to any point value of 12%, 15%, 18%, 20%, 22%, 24% or a range value between any two of them.
[0131] In the seventh aspect, the present invention provides a solid-state lithium-ion battery with silicon oxide as the negative electrode, including the silicon oxide negative electrode plate, a solid electrolyte and a positive electrode plate; or, including the silicon oxide negative electrode plate, a semi-solid electrolyte and a positive electrode plate.
[0132] This solid-state lithium-ion battery has high energy density, good safety performance and excellent cycle stability.
[0133] It is understandable that the solid-state lithium-ion battery includes a battery cell, which includes a silicon oxide negative electrode plate, a solid / semi-solid electrolyte and a positive electrode plate.
[0134] In a preferred embodiment, the solid electrolyte includes at least one of an oxide, a sulfide, a polymer electrolyte and an organic-inorganic composite electrolyte.
[0135] In a preferred embodiment, a solid electrolyte is placed on the surface of the silicon oxide negative electrode plate and press-formed to obtain a solid electrolyte layer integrated with the negative electrode.
[0136] More preferably, the sulfide comprises mLi2S-nP2S5 and Li 7-z PS 6-z A zAt least one of; wherein, 40≤m≤80, and m+n=100; A is selected from at least one of F, Cl, Br and I, and z=0.8~2.0.
[0137] The value of m mentioned above includes but is not limited to any point value of 40, 45, 50, 55, 60, 65, 70, 75, 80 or a range value between any two of them.
[0138] The value of z mentioned above includes but is not limited to any point value of 0.9, 1.0, 1.2, 1.4, 1.5, 1.7, 1.9 or a range of values between any two of them.
[0139] In a preferred embodiment, the positive electrode plate is mainly made of positive electrode active material, binder, conductive agent, electrolyte and current collector. The binder used in the positive electrode plate includes PTFE (i.e. polytetrafluoroethylene); the conductive agent includes vapor-deposited carbon fiber; the electrolyte includes at least one of oxide, sulfide, polymer electrolyte, organic-inorganic composite electrolyte and semi-solid electrolyte containing liquid, such as Li6PS5Cl, but not limited thereto.
[0140] In a preferred embodiment, the active material (i.e., positive electrode active material) used in the positive electrode plate includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, nickel-manganese layered oxide positive electrode material, lithium manganate, lithium-rich manganese-based positive electrode material, sulfur and lithium sulfide. It is understandable that the surface of the above active material may also have any conventional coating layer; the above active material may also be doped with conventional metal or non-metal elements.
[0141] In a preferred embodiment, when the positive electrode active material used in the positive electrode plate is sulfur and / or lithium sulfide, the positive electrode plate is mainly made of positive electrode active material, carrier, conductive agent, electrolyte and current collector. Among them, the mass fraction of the positive electrode active material is 30% to 70%, for example, 40%, 50% or 60%. The carrier includes porous carbon black, preferably BP2000 or Ketjen black. The conductive agent includes carbon black. The electrolyte includes at least one of an oxide, a sulfide, a polymer electrolyte, an organic-inorganic composite electrolyte and a semi-solid electrolyte containing a liquid. The type of electrolyte used in the positive electrode plate can be the same as the type of solid electrolyte used in the solid-state lithium-ion battery.
[0142] In a preferred embodiment, the semi-solid electrolyte is a polymer or a mixture thereof with a liquid electrolyte. The polymer includes injecting a liquefied polymer monomer, a lithium salt, a plasticizer and an initiator into the battery cell, and initiating the polymerization of the monomer under certain conditions after complete infiltration to form a solid-state battery. The polymer electrolyte also includes injecting a liquid electrolyte into the battery cell first, injecting a polymer monomer, a plasticizer and an initiator after aging and formation, and in-situ polymerization and gelation under certain conditions.
[0143] In an eighth aspect, the present invention provides an electrical device comprising the solid-state lithium-ion battery.
[0144] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0145] Example 1
[0146] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is SiO x , where x = 1, SiO x The particle size distribution is 4 to 6 μm.
[0147] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment comprises the following steps: mixing the silicon oxide negative electrode material and polyvinylidene fluoride at a mass ratio of 99:1, and adding N-methylpyrrolidone thereto to prepare a slurry. The slurry is applied to the surface of the copper foil and dried (the layer formed after the slurry is dried is hereinafter referred to as the material layer), and then rolled and cut to obtain the silicon oxide negative electrode sheet.
[0148] The solid-state lithium-ion battery provided in this embodiment is a half-cell, with a lithium-indium alloy sheet as a counter electrode, and the half-cell includes the silicon oxide negative electrode sheet, a solid electrolyte layer and a counter electrode sheet prepared as above. The preparation method of the solid-state lithium-ion battery is as follows: the Li6PS5Cl solid electrolyte powder is spread on the surface of the silicon oxide negative electrode sheet, and pressurized to form, the pressurization pressure is 280Mpa, and a solid electrolyte layer integrated with the negative electrode is obtained. Then the lithium-indium alloy counter electrode is attached to the other side of the solid electrolyte layer. The current collectors are placed on the negative electrode sheet side and the counter electrode side respectively, and the pressurized compound is pressed to a pressure of 10Mpa to obtain a solid-state lithium-ion battery.
[0149] Example 2
[0150] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is modified SiO xMaterials, specifically carbon-coated SiO x Materials, where x = 1, SiO x The particle size distribution is the same as in Example 1.
[0151] The method for preparing the silicon oxide negative electrode material provided in this embodiment comprises the following steps: x (x=1) and asphalt were mixed in a mass ratio of 9:1 and dispersed in tetrahydrofuran, and then dried and carbonized at 900℃ for 2h to obtain carbon-coated SiO x Material.
[0152] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the SiO x Replaced with the carbon-coated SiO x Material.
[0153] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0154] Example 3
[0155] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is the same as that in Embodiment 1.
[0156] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment comprises the following steps: mixing the silicon oxide negative electrode material, artificial graphite and polyvinylidene fluoride in a mass ratio of 50:49:1, and adding N-methylpyrrolidone thereto to prepare a slurry. The slurry is applied to the surface of the copper foil and dried (the layer formed after the slurry is dried is hereinafter referred to as the material layer), and then rolled and cut to obtain the silicon oxide negative electrode sheet.
[0157] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0158] Example 4
[0159] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is SiO x , where x = 1, SiO x It is a ball-milled material with a particle size distribution of 0.1 to 5 μm.
[0160] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the SiO xReplaced with the SiO x .
[0161] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0162] Example 5
[0163] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is modified SiO x Materials, specifically heat-treated SiO x Materials, where x = 1, SiO x The particle size distribution is the same as in Example 1.
[0164] The method for preparing the silicon oxide negative electrode material comprises the following steps: x Heat treatment was performed in an argon atmosphere to obtain SiO x Material; wherein, the heat treatment temperature is 1000℃ and the holding time is 2h.
[0165] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the SiO x Replaced with the heat-treated SiO x Material.
[0166] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0167] Example 6
[0168] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is modified SiO x Materials, specifically reduced SiO x Materials, reduced SiO x x in the material is 0.6, and the reduced SiO x The particle size distribution of the material is the same as that of Example 1.
[0169] The method for preparing the silicon oxide negative electrode material comprises the following steps: x (x=1 before reduction) was mixed with aluminum powder (reducing agent), sodium chloride (reducing aid) and aluminum chloride (reducing aid) in a mass ratio of 1:1:4:1.16, and sintered at 300°C for 12h under argon atmosphere to obtain a sintered product. The sintered product was washed three times with 1 mol / L dilute hydrochloric acid solution to obtain the reduced SiOx Material.
[0170] The method for preparing the silicon oxide negative electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the SiO x Replaced with the reduced SiO x Material.
[0171] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0172] Example 7
[0173] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is the same as that in Example 4.
[0174] The preparation method of the silicon oxide negative electrode sheet provided in this embodiment comprises the following steps: mixing the silicon oxide negative electrode material, Li6PS5Cl powder, carbon black and polyvinylidene fluoride in a mass ratio of 74:20:5:1, and ball milling for 2 hours at a speed of 300r / min to obtain a mixed material. The mixed material is rolled to obtain a mixed film, and then the mixed film is composited on a copper foil by heated rolling, and then cut to obtain a silicon oxide negative electrode sheet.
[0175] The solid-state lithium-ion battery provided in this embodiment includes the silicon oxide negative electrode plate, the solid electrolyte layer and the positive electrode plate prepared above. The preparation method of the solid-state lithium-ion battery is as follows: (1) Li6PS5Cl powder is spread on the surface of the silicon oxide negative electrode plate and pressed to form, and the pressing pressure is 280Mpa to obtain a solid electrolyte layer integrated with the negative electrode, that is, a negative electrode-solid electrolyte integrated film. (2) Lithium cobalt oxide coated with lithium niobate, Li6PS5Cl powder, vapor-deposited carbon fiber and polytetrafluoroethylene are mixed in a mass ratio of 70:30:3:0.1, and ball milled at a speed of 300r / min for 2h to obtain a mixed material. The mixed material is rolled to obtain a mixed film, and it is compounded on an aluminum foil by heating and rolling, and then cut to obtain a positive electrode plate. (3) The positive electrode plate prepared in step (2) is attached to the other side of the negative electrode-solid electrolyte integrated film prepared in step (1), and the negative electrode capacity is 1.1:1 to the positive electrode capacity. Current collectors were placed on the negative electrode sheet side and the counter electrode side, respectively, and pressurized to form a composite with a pressurized pressure of 280 MPa to obtain a solid-state lithium-ion battery.
[0176] Example 8
[0177] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is the same as that in Embodiment 1.
[0178] This embodiment also provides a pre-lithiation method for the silicon oxide negative electrode material, which comprises the following steps: x (x=1) was mixed with lithium powder (lithium supplement) at a mass ratio of 1:0.6, and an appropriate amount of n-hexane was added thereto, and then ball-milled at a speed of 200 r / min for 12 h, with a pause of 5 min every 0.5 h during the ball-milling period. After the ball-milling was completed, the pre-lithiated SiO x Slurry.
[0179] The method for preparing the silicon oxide negative electrode provided in this embodiment comprises the following steps: x The slurry is coated on copper foil, and after drying, rolling and cutting, the negative electrode sheet is obtained.
[0180] The preparation method of the solid-state lithium-ion battery provided in this embodiment is basically the same as that in Example 1, except that the negative electrode plate in Example 1 is replaced with the silicon oxide negative electrode plate prepared as described above in this embodiment.
[0181] Example 9
[0182] The silicon oxide negative electrode material for solid-state lithium-ion batteries and its pre-lithiation method and the method for preparing the negative electrode plate provided in this embodiment are the same as those in Example 8.
[0183] The solid-state lithium-ion battery provided in this embodiment includes the silicon oxide negative electrode plate, the solid electrolyte layer and the positive electrode plate prepared in the above embodiment. The preparation method of the solid-state lithium-ion battery is as follows: (1) Li6PS5Cl powder is spread on the surface of the above silicon oxide negative electrode plate and pressed into shape at a pressure of 280 MPa to obtain a solid electrolyte layer integrated with the negative electrode, that is, a negative electrode-solid electrolyte integrated film. (2) Elemental sulfur and Ketjen black are mixed in a mass ratio of 3:1, and then heat-treated at 160°C for 12 hours to obtain a sulfur-carbon material. The sulfur-carbon material, Li6PS5Cl powder and carbon black are mixed and ball-milled in a mass ratio of 40:50:10 to obtain a mixed material. Polytetrafluoroethylene accounting for 3% of the mass fraction is added to the mixed material, and the mixture is ball-milled at a speed of 300 r / min for 2 hours, and then the obtained mixed material is rolled to obtain a mixed film, and it is compounded on an aluminum foil by heated rolling, and the positive electrode plate is obtained after cutting. (3) The positive electrode sheet prepared in step (2) is attached to the other side of the negative electrode-solid electrolyte integrated membrane prepared in step (1). Current collectors are placed on the negative electrode sheet side and the positive electrode side respectively, and the pressurized composite is 280 MPa to obtain a solid-state lithium battery.
[0184] Example 10
[0185] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is SiO x, where x = 0.4, SiO x The particle size distribution is 0.1~2μm.
[0186] This embodiment also provides a pre-lithiation method for the silicon oxide negative electrode material and a method for preparing a negative electrode sheet, which includes the following steps: mixing the silicon oxide material with the binder PTFE at a mass ratio of 96:4, and after preliminary mixing, ball milling at a speed of 500r / min for 2h, and rolling the obtained mixed material to obtain a silicon oxide negative electrode film, and the mass ratio of the silicon oxide sheet to the lithium supplement lithium sheet is 1:0.35. The two are laminated, and they are compounded on a copper foil by heating and rolling (the silicon oxide material faces upward), and then cut to obtain a negative electrode sheet.
[0187] The solid-state lithium-ion battery provided in this embodiment includes the silicon oxide composite negative electrode plate, the solid electrolyte layer and the positive electrode plate prepared above. The preparation method of the solid-state lithium-ion battery is as follows: (1) Li6PS5Cl powder is spread on the surface of the silicon oxide composite negative electrode plate and pressed into shape at a pressure of 280 MPa to obtain a solid electrolyte layer integrated with the negative electrode, i.e., a negative electrode-solid electrolyte integrated film. (2) The high nickel ternary material (LiNi) coated with lithium niobate is coated with 0.8 Co 0.1 Mn 0.1 O2), Li6PS5Cl powder, vapor-deposited carbon fiber and polytetrafluoroethylene are mixed in a mass ratio of 70:30:3:0.1, and ball-milled at a speed of 300r / min for 2h to obtain a mixed material. The mixed material is rolled to obtain a mixed film, and it is compounded on an aluminum foil by heated rolling, and then cut to obtain a positive electrode sheet. (3) The positive electrode sheet prepared in step (2) is attached to the other side of the negative electrode-solid electrolyte integrated membrane prepared in step (1), and the negative electrode capacity is 1.1:1 to the positive electrode capacity. Current collectors are placed on the negative electrode sheet side and the positive electrode sheet side respectively for pressurization and compounding, and the pressurization pressure is 280Mpa to obtain a solid-state lithium-ion battery.
[0188] Embodiment 11
[0189] The silicon oxide negative electrode material for solid-state lithium-ion batteries provided in this embodiment is SiO x , where x = 1.3, SiO x The particle size distribution is 5 to 15 μm.
[0190] The pre-lithiation method of the negative electrode material, the preparation method of the silicon oxide negative electrode plate, and the preparation method of the solid-state lithium-ion battery provided in this embodiment are basically the same as those in Example 10, with the only difference being that the negative electrode material in Example 10 is replaced by the above-mentioned negative electrode material in this embodiment.
[0191] Comparative Example 1
[0192] This comparative example is a liquid lithium-ion battery of silicon oxide, which differs from Example 1 in that the solid electrolyte is replaced by an organic electrolyte and a diaphragm.
[0193] The preparation method of the liquid lithium ion battery is as follows: (1) SiO x (x=1, its particle size is the same as in Example 1), carbon black and polyvinylidene fluoride are mixed in a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone is added to prepare a slurry. The slurry is coated on a copper foil and cut to obtain a negative electrode. (2) A solution of 1 mol / L LiPF6 in ethylene carbonate and dimethyl carbonate (the volume ratio of ethylene carbonate and dimethyl carbonate is 1:1) is used as an electrolyte, a PE film is used as a battery separator, and lithium metal is used as a counter electrode to assemble a liquid lithium-ion battery.
[0194] Comparative Example 2
[0195] This comparative example is an all-solid-state battery with a silicon negative electrode, and the only difference from Example 1 is that silicon oxide is replaced by micron silicon, and its particle size distribution is 2 to 5 μm.
[0196] It is particularly noted that the discharge specific capacity referred to in the present invention in Examples 1-6, Example 8, and Comparative Example 1 is based on the SiO x The quality of the material, i.e. SiO x The specific capacity of the material; in Comparative Example 2, it is based on the mass of the Si material in its half-cell, that is, the specific capacity of the Si material; in Example 7, it is based on the mass of the positive electrode material (lithium cobalt oxide coated with lithium niobate) in its full cell. Since the ratio of the negative electrode capacity to the positive electrode capacity in the battery is fixed, it also reflects the negative electrode SiO x In Example 9, it is based on the mass of the positive electrode material (elemental sulfur) in the full battery. Since the ratio of the negative electrode capacity to the positive electrode capacity in the battery is fixed, it also reflects the negative electrode SiO x The capacity of the material; In Examples 10-11, it is based on the positive electrode material in the full battery (lithium niobate coated high nickel ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2), because the negative electrode capacity and positive electrode capacity ratio in the battery are fixed, it also reflects the negative electrode SiO x The capacity of the material.
[0197] The electrochemical performance of the batteries prepared in the above embodiments and comparative examples was tested respectively, and the test results are shown in Table 1 below.
[0198] Table 1 Electrochemical performance results of each group of batteries
[0199]
[0200]
[0201] In addition, if Figure 1 The charge and discharge curve of the battery prepared in Example 1 is shown in FIG. Figure 2 The charge and discharge curve of the battery prepared in Example 2 is shown in FIG. Figure 3 The figure shows the rate performance test diagram of the battery prepared in Example 4; Figure 4 The figure shows the cycle performance test diagram of the battery prepared in Example 4; Figure 5 The figure shows the cycle coulombic efficiency of the battery prepared in Example 4; Figure 6 The figure shows a cross-sectional view of the negative electrode sheet of the battery prepared in Example 4 after cycling. Figure 6 Anode in it represents the negative electrode, and Electrolyte represents the electrolyte layer; Figure 7 The figure shows the cycle performance test diagram of the battery prepared in Example 5; Figure 8 The reduced SiO obtained in Example 6 is shown. x XRD pattern of Fig. 9 The figure shows the cycle performance test diagram of the battery prepared in Example 6; Fig.10 The charge and discharge curve of the battery prepared in Example 7 is shown in FIG. Fig.11 The charge and discharge curve of the battery prepared in Example 8 is shown in FIG. Fig.12 The charge and discharge curve of the battery prepared in Example 9 is shown in FIG. Fig.13 Shown is a cross-sectional view of the negative electrode sheet of the battery prepared in Comparative Example 2 after cycling.
[0202] Specifically, the all-solid-state battery prepared in Example 1 has a -2 The current density was tested at 25°C and 100MPa. Figure 1 It can be seen that its first discharge capacity and charging capacity are 2207.4mAh·g -1 and 1182.6mAh·g -1 The first coulombic efficiency is 53.6%. The second cycle discharge capacity and charge capacity are 1252.4 mAh g -1 and 1156.2mAh·g -1 This shows that silicon oxide has a higher specific capacity.
[0203] The all-solid-state battery prepared in Example 2 has a -2 The current density was tested at 25°C and 100MPa. Figure 2 It can be seen that its first discharge capacity and charge capacity are 1039.4 mAh g -1and 717.2mAh·g -1 , the first coulombic efficiency is 69.0%. Comparison of Example 1 and Example 2 shows that carbon coating improves the conductivity of silicon oxide, thereby improving the first coulombic efficiency of silicon oxide, but reduces the specific capacity to a certain extent.
[0204] The all-solid-state battery prepared in Example 3 has a -2 The current density was tested at 25°C and 100 MPa. As shown in Table 1, the first discharge capacity and charge capacity are 1154.3 mAh g -1 and 688.0mAh·g -1 The first coulombic efficiency was 59.6%, and the 150-cycle cycle retention rate was 91.5%, indicating that the introduction of carbon materials is conducive to alleviating the volume effect of the silicon oxide negative electrode and improving the cycle stability.
[0205] The all-solid-state battery prepared in Example 4 was subjected to rate tests at 60°C and 100 MPa at different current densities. Figure 3 It can be seen that at 0.2 mA cm -2 , 0.4mA·cm -2 , 0.6mA·cm -2 , 0.8mA·cm -2 , 1.0mA·cm -2 , 1.5mA·cm -2 and 2.0 mA cm -2 The reversible capacities of -1 、1377.9mAh·g -1 、1397.7mAh·g -1 、1395.8mAh·g -1 、1388.4mAh·g -1 、1343.4mAh·g -1 and 1288.4mAh·g -1 . Demonstrated excellent rate performance. Figure 4 and Figure 5 The cycle performance and coulombic efficiency of Example 3 are shown at 1.0 mA cm -2 At a current density of 1044.3 mAh g -1 The reversible specific capacity and average coulombic efficiency are 99.7%, showing excellent cycle stability. Figure 6 It can be seen that the interface of the negative electrode plate is very smooth after the cycle, and there are no cracks caused by volume expansion and contraction.
[0206] The all-solid-state battery prepared in Example 5 was -2The current density was tested at 60°C and 100MPa. Figure 7 As can be seen from Table 1, the retention rate of silicon oxide after high temperature heat treatment is 67.2% after 150 cycles.
[0207] The all-solid-state battery prepared in Example 6 was -2 The charge and discharge tests were carried out at 60°C and 100MPa. Figure 8 It can be seen that after reduction modification, amorphous silicon oxide has three characteristic peaks at 28.4°, 47.3° and 56.1°, corresponding to silicon (111), (220) and (311) crystal planes (standard card number is 27-1402), indicating that part of the silicon oxide is reduced to form a single silicon phase. Fig. 9 As can be seen from Table 1, the cycle retention rate of the reduced silicon oxide is 76.4% after 150 cycles.
[0208] The all-solid-state battery prepared in Example 7 was used, with lithium niobate coated with lithium cobalt oxide as the positive electrode material, at 0.2 mA cm -2 The charge and discharge tests were carried out at 25°C and 100MPa at a current density of Fig.10 It can be seen that its first charge capacity and charging capacity are 102.2mAh g -1 and 55.2mAh·g -1 The specific capacity is calculated based on the positive electrode as the active material. The cycle retention rate after 150 cycles is 86.0%. This shows that silicon oxide can show good cycle performance in the actual all-solid-state full battery system.
[0209] The all-solid-state battery prepared in Example 8 was used for charge and discharge tests at 25°C and 100 MPa. -2 First charge and then discharge at a current density of Fig.11 It can be seen that the first lithium removal capacity of pre-lithiated silicon oxide is 1035.9 mAh g -1 The discharge capacity and charge capacity of the second cycle are 1129.6 mAh g -1 and 1053.1mAh·g -1 , the coulombic efficiency increased to 93.7%. After 150 cycles, the capacity retention rate was 89.3%, showing good cycle stability. This shows that the pre-lithiation method can well improve the coulombic efficiency of silicon oxide negative electrode.
[0210] The all-solid-state battery prepared in Example 9 is used, with the sulfur-carbon composite as the positive electrode and the pre-lithiated silicon oxide as the negative electrode, and the ratio of the negative electrode capacity to the positive electrode capacity is 1.5. Fig.12It can be seen that the first discharge capacity of the solid-state lithium-sulfur battery is 1333.4 mAh g -1 The subsequent second cycle charging and discharging capacity is 1561.6 mAh g -1 and 1550.8mAh·g -1 , the coulombic efficiency reached 99.3%. After 150 cycles, the capacity retention rate was 85.2%. It showed good cycle stability. It shows that the silicon oxide negative electrode can provide lithium source in all-solid-state lithium-sulfur batteries through this pre-lithiation method and has good cycle stability.
[0211] The all-solid-state full battery prepared in Example 10 was used, and the high-nickel nickel-cobalt-manganese ternary material coated with lithium niobate was used as the positive electrode material. -2 The charge and discharge tests were carried out at 25°C and 100 MPa at a current density of 1.38 W. As shown in Table 1, the first charge capacity and the charge capacity are 179.9 mAh g -1 and 171.5mAh·g -1 The specific capacity is calculated based on the positive electrode as the active material. The cycle retention rate after 150 cycles is 87.3%.
[0212] The all-solid-state full battery prepared in Example 11 was used, and the high-nickel nickel-cobalt-manganese ternary material coated with lithium niobate was used as the positive electrode material. -2 The charge and discharge tests were carried out at 25°C and 100 MPa at a current density of 1.38 W. As shown in Table 1, the first charge capacity and the charge capacity are 175.0 mAh g -1 and 159.6 mAh g -1 The specific capacity is calculated based on the positive electrode as the active material. The cycle retention rate after 150 cycles is 76.1%.
[0213] The liquid lithium-ion battery prepared in Comparative Example 1 has a large polarization during the first discharge. As shown in Table 1, the discharge capacity of Comparative Example 1 is only 15.2 mAh·g -1 The negative electrodes of Example 1 and Examples 4 to 7 have 99% silicon oxide, and exhibit better specific capacity and cycle performance in all-solid-state batteries.
[0214] The first discharge capacity of the all-solid-state battery using the silicon negative electrode prepared in Comparative Example 2 reached 3591.32 mAh g -1 , but the cycle performance is poor, and the cycle retention rate after 150 cycles is only 32.1%. Fig.13 It can be seen that a lot of cracks were generated on the interface of the negative electrode plate of Comparative Example 2 after the cycle.
[0215] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. Application of silicon oxide negative electrode material in the negative electrode of solid-state lithium-ion battery, characterized in that: The silicon oxide negative electrode material includes SiO x and / or modified SiO x Material, wherein 0<x<2.
2. The use of the silicon oxide negative electrode material according to claim 1 in a negative electrode of a solid-state lithium-ion battery, characterized in that: The SiO x And / or the modified SiO x In materials, 0.4≤x≤1.3; Preferably, the SiO x And / or the modified SiO x SiO in materials x The particle size is 0.1 to 20 μm, more preferably 0.1 to 5 μm; Preferably, the modified SiO x Materials include carbon-coated SiO x Materials, SiO x / carbon composites, element-doped SiO x Materials, heat treated SiO x Materials and reduced SiO x At least one of the materials; More preferably, the SiO x / The carbon material in the carbon composite material includes at least one of graphite, mesophase carbon microbeads, soft carbon and hard carbon; More preferably, the element-doped SiO x The doping element in the material includes at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn; More preferably, the heat-treated SiO x The material is SiO x The heat treatment is carried out at a temperature of 800 to 1200° C. and a holding time of 0.5 to 20 hours; the heat treatment atmosphere includes an inert atmosphere; More preferably, the reduced SiO x The material is SiO x The SiO x In materials, 0.4≤x≤1.
1.
3. A silicon oxide negative electrode material for a solid-state lithium-ion battery, characterized in that: The silicon oxide negative electrode material includes SiO x and / or modified SiO x Material, wherein 0<x<2.
4. The silicon oxide negative electrode material for solid-state lithium-ion batteries according to claim 3, characterized in that: The SiO x and / or modified SiO x In materials, 0.4≤x≤1.3; Preferably, the SiO x And / or the modified SiO x SiO in materials x The particle size is 0.1~20μm; Preferably, the modified SiO x Materials include carbon-coated SiO x Materials, SiO x / carbon composites, element-doped SiO x Materials, heat treated SiO x Materials and reduced SiO x At least one of the materials; More preferably, the SiO x / The carbon material in the carbon composite material includes at least one of graphite, mesophase carbon microbeads, soft carbon and hard carbon; More preferably, the element-doped SiO x The doping element in the material includes at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn; More preferably, the heat-treated SiO x The material is SiO x The heat treatment is carried out at a temperature of 800 to 1200° C. and a holding time of 0.5 to 20 hours; the heat treatment atmosphere includes an inert atmosphere; More preferably, the reduced SiO x The material is SiO x The product is prepared by reduction, wherein the reducing agent used for the reduction comprises at least one of metallic aluminum and metallic magnesium.
5. The method for preparing a silicon oxide negative electrode material for a solid-state lithium-ion battery according to claim 4, characterized in that: The modified SiO x The method for preparing the material includes at least one of the following methods (1) to (5): (1) Using vapor deposition or liquid coating-carbonization method to deposit SiO x Carbon coating is performed to obtain carbon-coated SiO x Material; (2) SiO x Mix evenly with carbon material to obtain SiO x / Carbon composite material; the carbon material comprises at least one of graphite, mesophase carbon microspheres, soft carbon and hard carbon; (3) SiO x After mixing with dopants and sintering, element-doped SiO x The dopant comprises a doping element including at least one of B, Al, Na, Mg, Ca, Ba, Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, Mo, Ge and Sn or an oxide thereof; (4)SiO x Heat treatment is performed in an inert atmosphere to obtain heat-treated SiO x Materials; the heat treatment temperature is 800 to 1200° C., and the holding time is 0.5 to 20 hours; the heat treatment atmosphere includes an inert atmosphere; (5)SiO x After mixing with a reducing agent, a reduction reaction is carried out to obtain reduced SiO x Material; the reducing agent includes at least one of metallic aluminum and metallic magnesium.
6. The pre-lithiation method for silicon oxide negative electrode material for solid-state lithium ion battery according to claim 3 or 4, characterized in that: The steps include: The silicon oxide negative electrode material is mixed with a lithium supplement agent and ground; the lithium supplement agent comprises at least one of metallic lithium, lithium silicide, naphthyl lithium and biphenyl lithium; And / or, the silicon oxide negative electrode material is made into a film, which is then stacked with a lithium sheet and pressurized for battery assembly.
7. Silicon oxide negative electrode plate, characterized in that: Mainly made of the silicon oxide negative electrode material for solid-state lithium-ion batteries as claimed in claim 3 or 4; Preferably, the silicon oxide negative electrode material is pre-lithiated by the pre-lithiation method as claimed in claim 6.
8. The method for preparing a silicon oxide negative electrode sheet according to claim 7, characterized in that: The steps include: Applying a first mixed material containing a silicon oxide negative electrode material and a solvent to the surface of a current collector; optionally, the first mixed material further comprises at least one of a carbon material, a conductive agent and an electrolyte; And / or, after rolling the second mixed material containing the silicon oxide negative electrode material and the binder into a film, it is compounded with the current collector by hot pressing; optionally, the second mixed material also includes at least one of a binder, a carbon material, a conductive agent and an electrolyte.
9. A solid-state lithium-ion battery, characterized in that: The invention comprises the silicon oxide negative electrode sheet, the solid electrolyte and the positive electrode sheet as claimed in claim 7, or comprises the silicon oxide negative electrode sheet, the semi-solid electrolyte and the positive electrode sheet as claimed in claim 7; Preferably, the solid electrolyte comprises at least one of an oxide, a sulfide, a polymer electrolyte and an organic-inorganic composite electrolyte; Preferably, the active material used for the positive electrode plate includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, nickel-manganese layered oxide positive electrode material, lithium manganese oxide, lithium-rich manganese-based positive electrode material, sulfur and lithium sulfide.
10. Electrical equipment, characterized in that: Comprising the solid-state lithium-ion battery as claimed in claim 9.
Citation Information
Patent Citations
Element-doped SiOx negative electrode composite material as well as preparation method and application thereof
CN106654194A
Silicon oxide composite negative electrode material for lithium ion battery and preparation method of silicon oxide composite negative electrode material
CN109524650A
Silicon-based negative electrode material and preparation method and application thereof
CN112349888A
Flexible silicon monoxide-based lithium battery negative electrode material, negative electrode piece and lithium battery
CN113363471A
Solid-state lithium ion battery pre-lithiation electrode and preparation method thereof
CN113451543A
Cited By
Composite silicon negative electrode material and preparation method and application thereof
CN120727806A